The Predict-Observe-Explain Model: Is It Effective to Improve Science Process Skills? - Fauzan Kurniawan*; Djukri Djukri; Nukhbatul Bidayati Haka (Jurnal Pendidikan Sains Indonesia, 2022)
Science process skills are one of the demands of new skills needed by students in the 21st century. One of the learning models that can sharpen science process skills is the predict-observe-explain (POE) model. Heretofore, research related to science process skills with POE model in understanding human digestive system material is still minimal. Therefore, this research needs to be done. This study aimed to analyze the effect of the POE model on improving students'  science process skills. This study used a quasy experiment, and research design of the matching only pretest-posttest design. This study's population was all VIII students of SMP Negeri 19 Bandar Lampung, Lampung, Indonesia, in 2020/2021 academic. The sample in this study used a cluster random sampling technique, so that this study used 60 students as the research sample. Data collection techniques in the form of tests and observation sheets of science process skills. Data analysis in this study consisted of two, namely the N-Gain test and hypothesis testing using the independent samples t-test test. The results showed that the results of the N-Gain test in the experimental class were 0.66 (medium category), while the control class is a score of 0.34 (medium category). Meanwhile, The results of the research on the independent samples t-test on science process skills are the sig value. 0.000, p0,05. This implies that POE model facilitates in improving students' science process skills on human digestive system